Gendered discourses in the American TV sitcom F.R.I.E.N.D.S / Chin Ee Wern - Chin , Ee Wern (2020)
The current research concentrates on analysing the gendered discourse in the television (TV) series of F.R.I.E.N.D.S, investigating how gender is portrayed as it depicts a representable degree of society today. The proposed findings are information as to how this sitcom reflects the gendered discourses that were common in that time and are still relevant today. This paper considers how sitcom creators want their audiences to be able to relate to what is shown on their programme, making it relatable to the audience, creating the problem of possible bias from the creators supporting stereotypes that only encourages the same mindset amongst society, bringing a need to analyse the sitcoms for discourses presented to the audience. The research utilises 4 episodes chosen from F.R.I.E.N.D.S, based on criteria of number of audience views, TV ratings upon airing, and presence of comments with traces of gender in clips of episodes posted on Youtube. The episodes were analysed with scenes containing traces of gendered discourses extracted as data, the data is then categorised with the identified gendered discourses. The data is then compared to case studies and examples from journal articles and official news websites to determine if the presented discourses in the sitcom supports or challenge stereotypes held by society. 4 main gendered discourses identified were the Gender Differences discourse, Hegemonic Masculinity discourse, the Compulsory Heterosexuality discourse, the Gender equality discourse, and other discourses also identified were the Dumb Blonde discourse, “the being a woman is an insult” discourse, the Positive Masculinity discourse, and the “women love to gossip” discourse. From the analysis of the data done, it has shown that majority of the discourses found reinforces the normative perceptions of gender, which explains its relatability to many audiences around the world that made it a worldwide success upon airing, though it is worth nothing that there instances found to also challenge some of the normative perceptions as well, indicating a slow but sure movement towards a more accepting society.